2017
DOI: 10.1016/j.nlm.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Reversible inactivation of the lateral hypothalamus reversed high reward choices in cost-benefit decision-making in rats

Abstract: The Lateral hypothalamus (LH) is an important component of the networks underlying the control of feeding and other motivated behaviors. Cost-benefit decision-making is mediated largely by the prefrontal cortex (PFC) which strongly innervates the LH. Therefore, in the current study, we conducted a series of experiments to elucidate the role of the perifornical area of the lateral hypothalamus (PeF-LH) in effort and/or delay-based decision-making. We trained different groups of rats in a delay-based and/or an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Genetic deletion of the neuronal calcium sensor-1, which reduces accumbens DA transmission, made mice less willing to work for food, but left food preference, responding for conditioned reinforcement, and the ability to represent changes in reward value intact (Ng et al, 2016). Inactivation of the lateral hypothalamus produced a low-effort bias as marked by a reduction in barrier climbing in the T-maze (Karimi et al, 2017). Glycine acts as both an inhibitory neurotransmitter and a co-agonist at the N-methyl-D-aspartate receptor, and recent studies indicate that the glycine uptake inhibitor bitopertin can reverse the effort-related effects of haloperidol in rats tested on the FR5/chow-feeding and T-maze barrier choice tasks (Yohn et al, 2017a).…”
Section: Neural Circuits and Transmitters Mediatingmentioning
confidence: 99%
“…Genetic deletion of the neuronal calcium sensor-1, which reduces accumbens DA transmission, made mice less willing to work for food, but left food preference, responding for conditioned reinforcement, and the ability to represent changes in reward value intact (Ng et al, 2016). Inactivation of the lateral hypothalamus produced a low-effort bias as marked by a reduction in barrier climbing in the T-maze (Karimi et al, 2017). Glycine acts as both an inhibitory neurotransmitter and a co-agonist at the N-methyl-D-aspartate receptor, and recent studies indicate that the glycine uptake inhibitor bitopertin can reverse the effort-related effects of haloperidol in rats tested on the FR5/chow-feeding and T-maze barrier choice tasks (Yohn et al, 2017a).…”
Section: Neural Circuits and Transmitters Mediatingmentioning
confidence: 99%
“…The intensity of the effort can be increased by increasing the height of the barrier; maximum heights of 25 or 30 cm are most commonly reported. In rats, barrier paradigms have been used successfully in lesion/inactivation studies (Walton et al, 2002;Rudebeck et al, 2006;Floresco and Ghods-Sharifi, 2007;Holec et al, 2014;Karimi et al, 2017), pharmacological investigations (Schweimer and Hauber, 2006;Bardgett et al, 2009;Mott et al, 2009;Pardo et al, 2012;Yohn et al, 2015a,b;Correa et al, 2018), and electrophysiological recordings (Hillman and Bilkey, 2010;Cowen et al, 2012;Mashhoori et al, 2018) to assess the contribution of different brain areas and neurochemical systems to decisions that require physical effort. However, the protocol has limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior research showed that LH inactivation disrupts effort and delay-based decision-making task and this document clarified there is a relationship among ACC/OFC, as the two important sites for decision-making, and LH (Karimi et al, 2017). The alteration in the neural firing rate in ACC or OFC could also be due to the elimination of neurotransmitters in the LH.…”
Section: Discussionmentioning
confidence: 57%
“…Li, Hu, & Lecea, 2014). More recent works have revealed cognitive processes, such as associative learning and memory, control feeding behavior (Petrovich, 2018) and, decision-making (Karimi et al, 2017) need the LH function and it seems that it may serve as a motivation-cognition interface processor in the brain. Behavioral and electrophysiological studies have suggested the significance of the functional connections between the PFC and the LH (Arikuni, 1976;Kita & Oomura, 1981;Oomura & Takigawa, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation